2020
DOI: 10.1590/s1984-29612020027
|View full text |Cite
|
Sign up to set email alerts
|

Canine leishmaniasis in the semi-arid region of Pernambuco, northeastern Brazil: epidemiology, factors associated with seropositivity and spatial analysis

Abstract: This study aimed to determine the seroprevalence, factors associated with seropositivity to Leishmania infection in dogs and spatial analysis in six municipalities in the semiarid region of Pernambuco, Brazil. Blood samples were collected from 462 dogs, 77 in each municipality, and used for serological analysis [dual path platform (DPP®) and enzyme-linked immunosorbent assay (ELISA)]. Clinical signs of dogs were evaluated and associated factors for Leishmania infection were analyzed using robust Poisson regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
(78 reference statements)
0
6
0
1
Order By: Relevance
“…Apesar das prevalências em Lagoa Grande (9,1%) e Santa Maria da Boa Vista (1,8%) terem sido mais baixas da mesorregião do São Francisco, Evaristo et al 38 . observaram, num estudo epidemiológico realizado nestas regiões, que estes municípios são zonas endêmicas com um elevado risco de transmissão.…”
Section: Discussionunclassified
“…Apesar das prevalências em Lagoa Grande (9,1%) e Santa Maria da Boa Vista (1,8%) terem sido mais baixas da mesorregião do São Francisco, Evaristo et al 38 . observaram, num estudo epidemiológico realizado nestas regiões, que estes municípios são zonas endêmicas com um elevado risco de transmissão.…”
Section: Discussionunclassified
“…Herein, it was observed that male dogs were mostly affected by the disease in Sergipe (OR = 2.52). According to Silva et al ( 2016 ) and Evaristo et al ( 2020 ), the prevalence of male dogs infected in the semiarid region of the Northeast is about 2.25 times higher than that in females, mainly in animals of 12 and 84 months of age.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies in the literature aim to assess the influence of biological factors, such as sex and age, on the positivity rate for leishmaniasis (Silva et al 2016 ; Campos et al 2017 ; Evaristo et al 2020 ). Herein, it was observed that male dogs were mostly affected by the disease in Sergipe (OR = 2.52).…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence of canine visceral leishmaniasis (CVL) varies widely depending on the geographic region, level of exposure to the vectors and type of test used ( Carvalho et al, 2020 ). For instance, in the state of Pernambuco, Brazil, prevalence rates from 2.4% ( Lins et al, 2018 ) to 42.8% ( Evaristo et al, 2020 ) have been detected. This serological information on dogs is useful from an epidemiological perspective, since canine cases precede human ones.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, early diagnosis in these animals may drive measures that should be implemented for maintaining good health status of dogs. With the aim of improving the prevention of canine infection, several risk factors have been assessed over time, and features such as living in rural areas or close to green areas, male sex and crossbreeding have been considered to be potential risk factors ( Araujo et al, 2016 ; Evaristo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%